Lives : An Exhibition of Artists whose work is based on other peoples' lives . - Boshier, Derek (London : Arts Council of Great Britain, 1979)
Atkinson, Conrad ; Barnard, Roger ; Best, Sue ; Brett, Guy ; Byrne, Peter ; Duffy ; Dugger, John ; Garrard, Rose ; Harrison, Margaret ; Hepple, Norman ; Hockney, David ; Jewell, Dick ; Johnston, Steve ; Kitaj, R.B. ; Lange, Darcy ; Levine, Paula ; Marlow, Peter ; McLean, Bruce ; O'Neill, Desmond ; Ovski ; Punk ; Redfern, David ; Scarfe, Gerald ; Schadeburg, Jurgen ; Symonds, Posy ; County Times ; Wegner, Fritz ; Weight, Carel ; Wells, Sue
biog. per kunstenaar
Engels
Lives : an exhibition of artists whose work is based on other peoples' lives, Serpentine Gallery, London, 03.03.1973 - 31.03.1973
boek